ALGAE AND WATER POLLUTION IN MAIII ESTUARY - Jiyalal Ram, M (Journal of Indian Fisheries Association, 2015)
Distribution of phytoplankton, chlorophyll a and phaeophytin was studied at different locations in theMahi estuary during 1982. The water quality at the discharge point was poor while the region away fromit was relatively unpolluted. The results indicated a wide range of variation in phytoplankton population(7.68-5010. 96x104 cells/1, chl. a 2.22-58.22 mg/m3)and phaeophytin (0.20-10.21 mg/nr3). The ratio of chl. a/phaeophytin were remarkably low at highly polluted stations. Higher abundance of the genera Oscillatoria and Nitzschia were recorded at polluted stations. The diversity of species at the unpolluted station was higher (1.56) as compared to the polluted station (1.07).